Economics of joint dominance - Markku Stenborg (The Research Institute of the Finnish Economy (ETLA), 2002)
Recent court rulings, e.g., in the Gencor and Airtours cases, seem to indicate that the legal concept of joint dominance in oligopolistic markets is equivalent to the economic concept of collusion. This paper argues that the enlargement of the dominance concept to also include oligopolistic dominance is sensible and based on widely accepted economic theory. I discuss how competitive assessment in case law has taken seriously some economics lessons, but ignored some others. Economists on one hand and lawyers and antitrust authorities on the other hand seem to speak past each other on these issues. This paper attempts to bridge this gap, and to clarify the concept of collective dominance. I also discuss some recent advances in economic theory and empirical economic evidence related to the oligopolistic dominance that is relevant to the competition policy. – oligopoly ; dominant position ; market power ; competition policy ; merger – – Viimeaikaiset EU:n tuomioistuinten päätökset esimerkiksi Gencorja Airtours-asiassa indikoivat, että juridiikassa käytetty yhteisen määräävän markkinaaseman käsite oligopolistisilla markkinoilla vastaa taloustieteen kolluusion käsitettä. Tässä tutkimuksessa argumentoidaan, että määräävän markkina-aseman käsitteen laajentaminen koskemaan myös oligopolistista määräävää asemaa on järkevä ja perustuu laajalti hyväksyttyyn talousteoriaan. Vaikka kilpailuoikeudellinen arviointi on tapauskäytännössä ottanut huomioon eräitä taloustieteen oligopoleja koskevia tuloksia, se on näyttänyt olleen välittämättä eräistä muista tuloksista. Lisäksi ekonomistit ja juristit näyttävät toisinaan puhuvan toistensa ohi. Tämä tutkimus pyrkii rakentamaan siltaa ekonomistien ja juristien välille ja selventämään oligopolistisen määräävän markkina-aseman käsitettä. Tutkimuksessa tarkastellaan eräitä taloustieteen uusia teoreettisia ja empiirisiä tuloksia, joilla on merkitystä oligopoleja koskevaan kilpailupolitiikkaan. – oligopoli ; määräävä markkina-asema ; markkinavoima ; kilpailupolitiikka ; yrityskauppa
Keywords: K21; L13; L40; L41; 330; Oligopol; Marktmacht; Wettbewerbspolitik; Fusion; International; Europa